Advances in traditional Chinese medicine for burn treatment: mechanisms, therapeutic approaches, and innovative preparations - Liu, Ying; Yu, Caiyuan; Dou, Tong; Shen, Yang; Li, He; Liu, Mengyan; Xie, Wenying; Zeng, Weijia; Feng, Zizhao; Huang, Ming; Zhu, Yizhun (Frontiers in Pharmacology, 2025)
Traditional Chinese Medicine (TCM) possesses a well-documented historical legacy and substantial clinical experience in treating burn injuries and diverse wound conditions. Grounded in TCM theory, therapeutic strategies incorporate herbal medicine and its external preparations, as well as TCM auxiliary treatment, forming a comprehensive treatment framework. A systematic evaluation of burn management, particularly recent advancements in TCM research, carries significant implications for both theoretical and clinical applications. This paper synthesizes information from a plethora of online resources to explicate the mechanisms of TCM in burn treatment from multifaceted perspectives. Specifically, a comprehensive collection of literature pertaining to TCM burn treatment from the past three decades was amassed from electronic databases including PubMed, CNKI, and Web of Science. A meticulous keyword information statistical analysis was performed on this corpus. The search strategy employed keyword clusters such as “traditional Chinese medicine, phytochemistry, or herbs” combined with “burn, scald, or skin wound”. The scientific nomenclature of plants was verified using “The Plant List” (www.plantsoftheworldonline.org). This review encapsulates the methodologies of burn treatment within TCM and underscores a multitude of herbs with burn-treating capabilities, including Arnebia euchroma (Royle ex Benth.) I.M.Johnst., Rheum palmatum L., Coptis chinensis Franch., Phellodendron chinense C.K.Schneid., Sanguisorba officinalis L., and Angelica sinensis (Oliv.) Diels, as well as natural borneol (from Dryobalanops aromatica C.F.Gaertn.), Frankincense (from Boswellia sacra Flück.), and Myrrh (from Commiphora myrrha (T.Nees) Engl.). The principal active ingredients identified are shikonin, emodin, berberine, ferulic acid, and curcumin; however, their mechanisms warrant further in-depth investigation. Notable strides have been made in the innovation and research of TCM in burn treatment. Beyond traditional external formulations, hydrogel, liposome, microsphere, and nanofibers have emerged as pivotal elements in burn management. These advanced materials have introduced an innovative drug delivery system by integrating the active components, thereby enhancing the efficacy of burn treatment.